Effect of mechanical and friction properties of coconut peel on processing and manufacturing processes - Renyan Yang; Shaofeng Ru; Xuanhao Li; Yangding Han (International Journal of Food Properties)
Coconut peel plays a critical role in the manufacturing and industrial processing of coconut-derived products. This study investigates the physical properties of coconut peel through systematic experimental testing. Results indicated that both the coconut stored 20 days (S20-C) fiber blocks and peel specimens exhibited significantly higher tensile strength compared to freshly harvested coconut (Fh-C) fiber blocks and peel, respectively. Specifically, the S20-C fiber block (2.76 MPa) and S20-C peel (171.91 MPa) demonstrated peak tensile strength under a crosshead displacement rate of 6 mm/min. Cutting energy analysis revealed that Fh-C fiber blocks required greater cutting energy than S20-C fiber blocks across varying storage durations. Furthermore, orientation-dependent testing showed that horizontally aligned coconut fiber blocks exhibited higher cutting energy resistance than vertically oriented counterparts, with horizontally positioned Fh-C fiber blocks achieving the maximum cutting energy value (6917.16 N/mm). Energy absorption capacity varied significantly under different storage conditions: Fh-C fiber blocks absorbed more energy than S20-C fiber blocks, while vertical fiber configurations surpassed horizontal orientations in energy absorption across both groups. The vertically aligned Fh-C fiber block displayed the highest energy absorption capacity (17,830.25 N/mm). Tribological characterization indicated that S20-C fiber samples possessed a higher average coefficient of friction compared to Fh-C specimens. This study provides essential quantitative data to advance mechanized manufacturing and processing technologies for coconut-based products.